MIND MAPPING PLUS DEVELOPMENT AS LEARNING STRATEGY ON NERVOUS SYSTEM SUBJECT AT SENIOR HIGH SCHOOL - BUSTAN ANWAR RR (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Giving questionnaires to high school students showed that they have difficulties in understanding the biology subject. Therefore, students need to be taught a kind of learning strategy that can make them understand the biology materials easily. One alternative is using a Mind Mapping Plus. This research aims to describe the feasibility of The Mind Mapping Plus and the students’ response. The Mind Mapping Plus was developed using Fenrich model. The feasibility data were obtained from experts and practitioner reviews. Students’ responses were obtained from questionnaire. The results showed that Mind Mapping Plus is feasible and categorized good. Students respond to the use of Mind Mapping Plus positively. Keywords: learning strategies, Mind Mapping Plus, Human Nervous System.